Pengaruh Konsentrasi Ragi dan Lama Waktu Fermentasi Terhadap Yield Bioetanol Ubi Cilembu - Martha Susana Rischa; Zuhdi Ma'sum; Fikka Kartika Widyastuti (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2021)
This study aims to determine the effect of the amount of yeast and the length of time of fermentation on % yield of cilembu sweet potato bioethanol produced from the fermentation process. The stages of the research method include: sample preparation of cilembu sweet potato, hydrolysis process, fermentation process and bioethanol purification. Sample preparation was carried out by cutting, washing, drying and grinding. The hydrolysis process uses the acid hydrolysis method, namely 21% HCl. Yeast Saccharomyces cereviceae was used in the fermentation process with 5, 6, and 8 days of fermentation time and 5 grams and 6 grams of yeast mass variations. Meanwhile, the distillation method is used in the bioethanol purification process. Next, the percent yield of the bioethanol produced is determined. The results showed that the yield of bioethanol using 5 grams of yeast with each fermentation time was 5 days: 0.86%, 6 days: 1.94%, and 8 days: 0.97%. While the % yield of bioethanol used 6 grams of yeast each with variations in fermentation time of 5 days: 1.25%, 6 days: 1.69%, and 8 days: 1.6%. The highest bioethanol yield was found on day 6 with the use of 5 grams of yeast.